Unraveling a cytoplasmic role for hnRNP D in the in vivo mRNA destabilization directed by the AU-rich element - Loflin, Paul (Cold Spring Harbor Laboratory Press, 1999)
AU-rich RNA-destabilizing elements (AREs) have become a paradigm for studying cytoplasmic mRNA turnover in mammalian cells. Though many RNA-binding proteins have been shown to bind to AREs in vitro, trans-acting factors that participate in the in vivo destabilization of cytoplasmic RNA by AREs remains unknown. Experiments were performed to investigate the cellular mechanisms and to identify potential trans-acting factors for ARE-directed mRNA decay. These experiments identified hnRNP D, a heterogeneous nuclear ribonucleoprotein (hnRNP) capable of shuttling between the nucleus and cytoplasm, as an RNA destabilizing protein in vivo in ARE-mediated rapid mRNA decay. Our results show that the ARE destabilizing function is dramatically impeded during hemin-induced erythroid differentiation and not in TPA-induced megakaryocytic differentiation of human erythroleukemic K562 cells. A sequestration of hnRNP D into a hemin-induced protein complex, termed hemin-regulated factor or HRF, correlates well with the loss of ARE-destabilizing function in the cytoplasm. Further experiments show that in hemin-treated cells, ectopic expression of hnRNP D restores the rapid decay directed by the ARE. The extent of destabilizing effect varies among the four isoforms of hnRNP D, with p37 and p42 displaying the most profound effect. These results demonstrate a specific cytoplasmic function for hnRNP D as an RNA-destabilizing protein in ARE-mediated decay pathway. These in vivo findings support an emerging idea that shuttling hnRNP proteins have not only a nuclear but also a cytoplasmic function in mRNA metabolism. The data further imply that shuttling hnRNP proteins define, at least in part, the nuclear history of individual mRNAs and thereby influence their cytoplasmic fate.